Predictive modelling in food - Perez-Rodriguez, Fernando (Cambridge Scholars Publisher, 2019)
This volume brings together papers detailing the latest advances in the field of predictive microbiology in foods presented at the 10th International Conference on Predictive Modelling in Food, held in Córdoba, Spain, in 2016. Predictive microbiology is a scientific area providing mathematical models to predict microbial behaviour in the food environment, providing valuable tools for food risk managers, food scientists and the food industry as a whole. The book introduces the reader to the most used and recognized modelling techniques for food, providing a thorough overview of this discipline.